Diseño de capas de rodadura básicas granulares con adición de melaza de caña, para vías de tercer orden y vecinales - Allauca Avilés, Lenin Stiven (2022)
Ecuador's road network is made up of a large number of unpaved country roads, which facilitate land mobility. However, the roads are not in the best condition due to insufficient bearing capacity or because the roads don't have an improvement material, which influences their useful life. The main problem of road surfaces is the rapid wear and the release of dust, so several studies have proposed using stabilizers to improve this layer. Even so, there is little information on sugarcane molasses as a soil stabilizer in Ecuador. For this reason, in this research, we propose to measure the bearing capacity by incorporating cane molasses into a basic granular wearing layer specified for low-traffic roads with ballasted sandy subgrades. Due to this stabilizer, it is estimated that its CBR bearing value will increase. The research design was a pure experimental type, carried out through direct observation using laboratory tests required by the "Ministerio de Transporte y Obras Publicas" in the Ecuadorian road standard "NEVI-12 Vol. 3" in order to determine the influence of this additive on the mechanical properties of basic granular wearing courses. The optimum dosage of granular material for road surfaces corresponds to 60% fine aggregate and 40% coarse aggregate. Finally, it was determined that the optimum content of cane molasses corresponds to 2.5%, increasing the road surface's bearing capacity from 92.9% to 207.4% and providing plasticity of 3.4%, which helps maintain the cohesion between the pavement particles.